(untitled) (LIS TODAY, 2026)
This study aims to present a bibliometric investigation of the “Journal of Library Management (JLM)” for the period from 2015 to 2022. Furthermore, to analyze the current research trends in the field of library and information science published in the “Journal of Library Management” is the purpose of this study. This analysis covers mainly the geographical and chronological distribution of articles, the number of references cited, the length of articles, the authorship pattern, prolific authors, etc. The study explored that a total of 86 articles have been published during the period of study, and on average, 5.37 articles have been published per issue. Similarly, a total of 150 authors have contributed to the journal, out of which 97 were male and 53 were female authors. The study also finds that 40 articles have been authored by two authors, whereas 33 articles have been authored by single authors. Out of a total of 1,285 references cited in all 86 articles published during the period of study, 535 references have been given in the range of 11-20 references, while 289 references have been given in the range of >30 references. The study concludes that all the major research areas of library and information science have been covered in the source journal “JLM” by authors from India as well as from abroad.